Detection of Severe Turbulence Induced by Convection Using Numerical Modeling Over North Sumatra on 24 October 2017 - David Karunia Sianturi; Yosafat Donni Haryanto (Indo Green Journal, 2026)
This study diagnosed the severe turbulence event over North Sumatra on 24 October 2017 using numerical modeling and lognormal mapping of eddy dissipation rate (EDR). The Weather Research and Forecasting model was used to reproduce the convective environment associated with the event, and the simulated cloud field was evaluated against Himawari-8 visible imagery. The model reproduced the main convective band and the overall organization of the deep convective clouds reasonably well. Two raw turbulence diagnostics, and , were then converted to EDR using the lognormal mapping technique. Both diagnostics showed distributions broadly consistent with a lognormal shape, indicating their applicability for EDR conversion. The resulting EDR fields showed that the based mapping produced a broader and more distinct moderate-to-severe turbulence area near the reported encounter location than the based mapping. These results suggest that the severe turbulence event was dynamically consistent with convection-induced turbulence and that the based EDR mapping, a more realistic representation of the reported turbulence intensity.